New species of Casinaria and a key to the genera of Campopleginae (Hymenoptera: Ichneumonidae) in New Zealand - Ward, Darren (Zootaxa, 2026)
The genus Casinaria Holmgren, 1859 (Ichneumonidae, Campopleginae) from New Zealand is revised, and ten new species are described: Casinaria asessilis Ward sp. nov., C. aucklandensis Ward sp. nov., C. dublinbaya Ward sp. nov., C. floccosae Ward sp. nov., C. fulviventris Ward sp. nov. C. hartnetti sp. nov., C. kendalli sp. nov., C. maculipes sp. nov., C. mercurialis sp. nov., and C. saundersi sp. nov. Several species have host records. A key to the genera of Campopleginae and a key to the species of Casinaria in New Zealand are provided.